Sunscreen Activity Determination on Hippobroma Longiflora Leaves Extracts Affected to Differences in Simplicia Treatments and Extraction Techniques - Awaly Ilham Dewantoro; Selly Harnesa Putri; Efri Mardawati; Desy Nurliasari (Department of Chemistry, Faculty of Science and Technology, UIN Sunan Gunung Djati Bandung, 2022)
Various weeds in paddy rice fields could be utilized as natural polyphenols sources, one of them was kitolod (Hippobroma longiflora (L.) G.Don). Kitolod was widely utilized as traditional medicine by several community groups because of its polyphenols content. Recent trends showed kitolod could be valorized as additive matters in sunscreen products. Polyphenols content, especially flavonoids were able to absorb dangerous spectrum in sunray radiation and it is related to sunscreen activity. This study aimed to evaluate the differences in simplicia treatments and extraction techniques towards total polyphenols content and sunscreen activity on kitolod leaf extracts. Solvent-cold extraction techniques were deployed in this study that consist of water infusion and ethanolic maceration for 24 hours at ambient temperature. Extracts were analyzed by spectrophotometric measurement to determine total phenolics content (TPC), total flavonoids content (TFC), and sunscreen activity by deploying Folin-Ciocalteu assay, AlCl3 colorimetric assay, and Mansur approached assay, respectively. Dry kitolod leaves were extracted by ethanolic maceration techniques provided high yields (15.5±0.3%), high TPC (17.9±0.3 mg GAE/g of solids), high TFC (25.9±0.4 mg QE/g of solids), and moderate sunscreen activity (SPF 11.0±0.1). The results indicated kitolod could be valorized as natural polyphenols sources and additive matters in any cosmetical sunscreen products.